Changes of probabilities in different wind grades induced by land use and cover change in Eastern China Plain during 1980–2011. (22nd March 2016) - Zha, Jinlin; Wu, Jian; Zhao, Deming
Abstract: The differences of the near‐surface wind speed (SWS) between the frictional wind model (FWM) and the observation are used to reflect the impacts of land use and cover change (LUCC) on SWS in Eastern China Plain (ECP). Results show that LUCC makes the range of SWS narrow, which had significantly weakening effect to stronger wind than weaker wind. In addition, the decrease of probabilities for observed gentle breeze (GB), moderate breeze (MB), and wind speed greater than or equal to 8 m s −1 (WSGE8) are more significant in large cities than that in small cities.